The Right to Adequate Child Support in Jordan: The Implementation of the UN Convention on the Rights of the Child. (19th May 2022) - Hilal, Ghofran; Al-Zu'bi, Hadeel; Hilal, Thawab
Abstract: Child support is an internationally recognized child's right. It should be viewed as a basic human right and therefore treated accordingly by lawmakers and legal practitioners. In Jordan, child support is mainly regulated by the Jordanian Personal Status Law (JPSL), which is directly derived from Islamic law. However, Jordan is also a signatory state of the United Nation Convention on the Rights of the Child of 1989 (CRC). Thus, it is crucial to understand what the JPSL is currently pertaining to child support while presenting and comparing its provisions with the obligations under the International Human Rights Law. The article outlines ways in which the domestic judiciary system could utilize the CRC to provide an effective implementation of a child's right to adequate financial support in line with the main principles of the CRC.